2009
DOI: 10.1002/ijc.24210
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐carbinol inhibits MDA‐MB‐231 breast cancer cell motility and induces stress fibers and focal adhesion formation by activation of Rho kinase activity

Abstract: Indole-3-carbinol (I3C), a phytochemical derived from cruciferous vegetables such as broccoli and Brussels sprouts, has potent anti-proliferative effects in human breast cancer cells and has been shown to decrease metastatic spread of tumors in experimental animals. Using chemotaxis and fluorescent-bead cell motility assays, we demonstrated that I3C significantly decreased the in vitro migration of MDA-MB-231 cells, a highly invasive breast cancer cell line. Immunofluorescence staining of the actin cytoskeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 64 publications
3
26
1
1
Order By: Relevance
“…The breakdown products from indolic glucosinolates have been identified as phytoalexins in various Brassica species, suggesting that they have a role in plant defence (Pedras et al, 2003(Pedras et al, , 2006. Furthermore, indole-3-carbinol is a potential chemopreventive agent (Brew et al, 2009;Tolonen et al, 2002) and thus Chinese cabbage could be a good candidate for future breeding programmes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakdown products from indolic glucosinolates have been identified as phytoalexins in various Brassica species, suggesting that they have a role in plant defence (Pedras et al, 2003(Pedras et al, , 2006. Furthermore, indole-3-carbinol is a potential chemopreventive agent (Brew et al, 2009;Tolonen et al, 2002) and thus Chinese cabbage could be a good candidate for future breeding programmes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, indole-3-carbinol, the hydrolysis product derived from glucobrassicin, is thought to modulate biotransformation enzyme activity and act as an anticarcinogen (Brew et al, 2009). However, the negative aspects of these compounds have been a major focus of research due to their ''antinutritional" or goitrogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the activation of Rho-kinase leads to an inhibition of motility in human breast cancer cells [27]. The active vitamin D metabolite 1,25-dihydroxyvitamin D3, used as an anticancer agent, inhibits the proliferation and promotes the differentiation to a normal adhesive epithelial phenotype of human colon cancer cells via augmentation of cytosolic Ca 2+ concentration and activation of RhoA/Rho-kinase [28].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SOT17 and SOT18, for example, could lead to more nitriles and epithionitriles, due to hydrolysis of the respective Gls and thereby contribute to a better plant defense. An overexpression of SOT16 could lead to a higher indolic Gl concentration, which hydrolysis products are assumed to have anti-carcinogenic properties (Brew et al, 2009). The relatively high number of SOT16s in B. rapa could lead to the assumption of a higher indolic Gl concentration, but it was shown that in general B. oleracea have the highest indolic Gl content (B. rapa: 1.58 mmol g À1 DW, B. oleracea: 7.99 mmol g À1 DW).…”
Section: Discussionmentioning
confidence: 99%